2008
DOI: 10.1016/j.juro.2008.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Postoperative C-Reactive Protein Level in Patients With Metastatic Renal Cell Carcinoma Undergoing Cytoreductive Nephrectomy

Abstract: The current study indicated that C-reactive protein kinetics would predict the clinical course of patients with metastatic renal cell carcinoma who underwent cytoreductive nephrectomy. Larger confirmatory studies would be warranted to validate the current results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 18 publications
3
28
1
Order By: Relevance
“…48 We showed that perioperative dynamic changes in CRP concentration, CRP kinetics, predicted the clinical course of metastatic RCC patients treated with cytoreductive nephrectomy. 50 In this study, patients were divided into three groups based on their preoperative CRP levels and the status of CRP normalization 1 month after the operation. Patients whose preoperative CRP was not elevated (CRP <5 mg/L) were assigned to the non-elevated CRP group.…”
Section: Crp Kinetics In Renal Cell Carcinomamentioning
confidence: 99%
“…48 We showed that perioperative dynamic changes in CRP concentration, CRP kinetics, predicted the clinical course of metastatic RCC patients treated with cytoreductive nephrectomy. 50 In this study, patients were divided into three groups based on their preoperative CRP levels and the status of CRP normalization 1 month after the operation. Patients whose preoperative CRP was not elevated (CRP <5 mg/L) were assigned to the non-elevated CRP group.…”
Section: Crp Kinetics In Renal Cell Carcinomamentioning
confidence: 99%
“…Patients whose postoperative nadir CRP decreased to within normal limits (<1.0 ng/ml) exhibited significantly better disease-specific survival compared with patients whose CRP remained elevated (P=0.0025) (13). Subsequently, Tatokoro et al (14) reported that the prognosis of patients whose CRP normalized (to <0.5 mg/dl) following cytoreductive nephrectomy and the prognosis of patients without preoperative elevated CRP were better compared with the prognosis of patients whose CRP did not normalize after surgery. These investigators concluded that CRP kinetics may predict the clinical course of patients with metastatic RCC who undergo cytoreductive nephrectomy (14).…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, Tatokoro et al (14) reported that the prognosis of patients whose CRP normalized (to <0.5 mg/dl) following cytoreductive nephrectomy and the prognosis of patients without preoperative elevated CRP were better compared with the prognosis of patients whose CRP did not normalize after surgery. These investigators concluded that CRP kinetics may predict the clinical course of patients with metastatic RCC who undergo cytoreductive nephrectomy (14). Saito et al (15) reported that CRP kinetics affect survival in patients with metastatic RCC treated with immunotherapy, metastasectomy, or both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations